Audio-visual media to improve sexual-reproduction health knowledge among adolescent - Sitti Nur Djannah; Sulistyawati Sulistyawati; Tri Wahyuni Sukesi; Surahma Asti Mulasari; Fatwa Tentama (International Journal of Evaluation and Research in Education (IJERE), 2020)
Lacking knowledge among adolescents affects their understanding of some problems related to sexual-reproduction health. Electronic media recognized as the favored source of information for adolescents. This research aimed to assess the effect of audio-visual media to the increasing of sexual-reproduction knowledge. We conducted a before and after without control informal experimental study design into 153 students in the 1st-3rd grade of junior high school. The effect of the intervention was assessed through the difference between pre- and post-intervention by using the Wilcoxon test. The mean score of the respondent pre and post-intervention was significantly increasing. The audiovisual increased the knowledge of the adolescent regarding sexual-reproduction health